MODELLING FACTOR OF BUILT-UP SATURATION IN THE CITY CENTRE OF KUALA LUMPUR AND PENANG - Abang Mahmud, Dayang Shahrizat; Yin, Izuandi; Tan, Mou Leong; Mohamad, Diana; S. Muthuveeran, Adam Aruldewan (PLANNING MALAYSIA, 2023)
In Kuala Lumpur and Penang City Centres, different built-up patterns have emerged based on the gazetted permitted development for the past few years. Since independence, Kuala Lumpur and Penang have experienced substantial growth and modernization throughout the years. Both cities have rapid growth despite the fact that the character of the cities has evolved in built-up patterns from bungalow and mansion settlements due to transporting tin from the mining area (Kuala Lumpur City Centre) into the golden triangle of Klang Valley; colonial areas and ancient shops due to resource transportation to the harbour (Georgetown) into UNESCO World Heritage Sites. There is development control, which is regulated to protect the distinctiveness of the city, including limiting its ability to grow and controlling the saturation of land. This demonstrates how these two city centres have largely concentrated buildings in Kuala Lumpur while Penang is maintaining its conservation plan. The research was conducted to observe the changes in development for both cities (1km radius) from 2015 until 2023 by using the method of overlay analysis between image processing and remote sensing data using the Geographic Information System (GIS) and the USGS Earth Explorer. This assessment is crucial in determining the saturated area, the pattern of built-up development, and the factor of development force.